Schwannoma of the phrenic nerve. A case report - Chudacek, Josef; Bohanes, Tomas; Szkorupa, Marek; Stasek, Martin; Hanuliak, Jan; Skanderova, Daniela; Klos, Dusan (Biomedical papers, 2024)
Background. Neurogenic tumors are the third most common tumors occurring within the mediastinum. Predominantly completely asymptomatic, they are most often found in the posterior mediastinum, although they may also be located, albeit rarely, in the middle mediastinum. Thus, in the cases of tumors localized in the middle mediastinum, schwannomas of the phrenic nerve must always be considered. Case Report. In this case, a male patient presented with a tumor of the middle mediastinum. PET/CT scan determined that it was a circumscribed tumor without signs of dissemination. However, due to the tumor's location, a preoperative biopsy of the tumor was not possible. Therefore, the patient underwent videothoracoscopic extirpation of the tumor, including the necessary resection of the phrenic nerve that passed through the centre of the tumor. Subsequent histological analysis definitively confirmed a schwannoma with low proliferative activity. Conclusions. Differential diagnosis of mediastinal tumours is very difficult; however, in the case of circumscribed tumours not invading the surrounding tissues, proceeding to surgical revision, with the complete removal of the tumour, is possible, even without determining the histological nature. Minimally invasive surgical techniques dominate the treatment of neurogenic tumors of the mediastinum; they are associated with minimal complications and allow a rapid return of the patient to their normal activities.
Keywords: schwannom; nervus phrenius; mediastinum; videothoracoscopic resection; neurogenic tumors